2001
DOI: 10.1073/pnas.101093498
|View full text |Cite
|
Sign up to set email alerts
|

Rapid plant diversification: Planning for an evolutionary future

Abstract: Systematic conservation planning is a branch of conservation biology that seeks to identify spatially explicit options for the preservation of biodiversity. Alternative systems of conservation areas are predictions about effective ways of promoting the persistence of biodiversity; therefore, they should consider not only biodiversity pattern but also the ecological and evolutionary processes that maintain and generate species. Most research and application, however, has focused on pattern representation only. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
115
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(118 citation statements)
references
References 58 publications
0
115
0
3
Order By: Relevance
“…We find that translated into species numbers, the Cape flora has more than twice as many species (on average 655 species per Ϸ12,100 km 2 grid cell more; maximum: 1,637) per unit area than expected given its contemporary environment and topography, confirming, from a global perspective, its outstanding richness (44). The potential causes of the unique plant diversity of the Cape region are still debated and include climatic shifts from summer to winter rains starting in the Oligocene, pollinator specialization, mesoscale habitat specialization, and fire regimes, giving rise to an enormous diversification in some clades (45,45). Crucially, we find that many regional differences in species richness that have classically been attributed to historical factors can also be predicted by contemporary differences in the environment.…”
Section: Resultsmentioning
confidence: 87%
“…We find that translated into species numbers, the Cape flora has more than twice as many species (on average 655 species per Ϸ12,100 km 2 grid cell more; maximum: 1,637) per unit area than expected given its contemporary environment and topography, confirming, from a global perspective, its outstanding richness (44). The potential causes of the unique plant diversity of the Cape region are still debated and include climatic shifts from summer to winter rains starting in the Oligocene, pollinator specialization, mesoscale habitat specialization, and fire regimes, giving rise to an enormous diversification in some clades (45,45). Crucially, we find that many regional differences in species richness that have classically been attributed to historical factors can also be predicted by contemporary differences in the environment.…”
Section: Resultsmentioning
confidence: 87%
“…The phylogeny of this genus is still unknown, so the place of origin of Sebaea can not be suggested yet. Examples showed that the species richness in the Cape flora probably resulted from rapid and recent (7-8 MY) diversification (Cowling and Pressey, 2001;Richardson et al, 2001b). This might also be the case for Sebaea.…”
Section: Biogeographical Implicationsmentioning
confidence: 96%
“…This is critical to identifying corridors or ''landscape linkages'' that facilitate the continuity among the less damaged habitats and help secure biological processes critical to functioning ecosystems (37). The approach is well exemplified in protocols established by Cowling et al (38) for maintenance of viable ecological and evolutionary processes in the Cape Floristic Region, a remarkable area containing 12,000 plant species, 80% of which are endemic.…”
Section: Near-term Scenarios For Recovery: a Strategymentioning
confidence: 99%